Aktivitas Antibakteri Kombinasi Ekstrak Bawang Putih (Allium Sativum L.) dan Ekstrak Kunyit (Curcuma Longa L.) Terhadap Propionibacterium acnes - Aruan, Maroloan; Ayuningtyas, Nurista Dida; Ismena, Arnita Vania Naomi (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to see the antibacterial activity of ethanol extracts of garlic and turmeric in single and combination against Propionibacterium acnes. This type of research is an experimental study, which involves testing the antibacterial activity of ethanol extracts of garlic and turmeric, both singly and in combination, against Propionibacterium acnes bacteria. The research process included extraction, antibacterial activity testing using the pitting method, and data analysis to see significant differences between treatment groups. Garlic bulbs and turmeric rhizomes were macerated with 70% ethanol solvent and tested for antibacterial activity on each of the ethanol extracts of garlic (5%; 7.5%; 10%) and turmeric (2.5%; 5%; 7.5%) as well as the concentration of Garlic:Turmeric Extract Combination (5%:2.5%; 7.5%:2.5%; 5%:5%; 7.5%:5%). The results showed that (1) the results of antibacterial activity of ethanol extract of garlic were 8.20 ± 0.08; 9 ± 0.26; 10.43 ± 0.25 mm (included in the moderate category); (2) the results of antibacterial activity of turmeric extract were 3.19 ± 0.23; 3.56 ± 0.35; 4.43 ± 0.52 mm (included in the weak category), respectively; (3) the results of antibacterial activity on the combination of extracts 2.86 ± 0.72; 3.64 ± 0.08; 4.42 ± 0.16; 5.31 ± 0.76 mm (included in the weak category); (4) the results of data analysis obtained are that there are significant differences in antibacterial activity between treatment groups.